Germplasm conservation of Phyllanthus virgatus G. Forst. by encapsulation of In vitro derived leaf segments - Magendiran, M.; Vijayakumar, K. K.; Thambiraj, J.; Mahendran, S. (Current Botany, 2022)
The present study describes an efficient plant regeneration system for in vitro propagation of Phyllanthus virgatus through leaf explant. The leaf explants were cultured on Murashige & Skoog (MS) medium supplemented with BAP (1.5 mg L-1) and NAA (0.9 mg L-1 for efficient callus induction (82.26%). The maximum percentage of shoots (77.85%) was developed from BAP (2.0 mg L-1) and GA3 (0.5 mg L-1). The efficient rooting response (76.28%) was noted on a nutrient medium containing NAA (1.5 mg L-1) and IBA (0.2 mg L-1). Regenerated plantlets were successfully acclimatized and hardened off inside the culture room and then transferred to green house with a 72% survival rate.